Willingness to Pay for Mangroves’ Coastal Protection: A Case Study in Santo Angel, Calauag, Quezon, Philippines - Gagarin, Wesley; Eslava, Decibel F.; Ancog, Rico; Tiburan Jr, Cristino L.; Ramos, Noelynna (Forest and Society, 2022)
The mangroves in Santo Angel in the municipality of Calauag, Quezon Province in the Philippines, provide a wide array of ecological services that range from provisioning of resources and habitat to various floral and faunal species to regulating services including coastal protection. Coastal protection from mangroves is needed by the local community as Santo Angel is susceptible to typhoons and storm surges. However, the mangrove’s ability to provide coastal defense has considerably declined in the past decades due to overexploitation. Using the double-bounded dichotomous choice contingent valuation method, the willingness to pay (WTP) of the local community for a hypothetical mangrove rehabilitation project aligned towards coastal protection was determined. A total of 210 households were involved in the survey. The results show that 79% of the 210 households expressed WTP for the mangrove rehabilitation project. Furthermore, the mean willingness to pay (MWTP) for the mangrove rehabilitation project was computed at Php 15.44 (USD 0.29) per household per month or equivalent to Php 86, 525.76 (USD 1,659.41) per year for the total number of households in Santo Angel. Findings of the logistic regression analysis revealed that sex, age, membership in environmental organizations, and awareness on both the economic importance and the ecological services provided by mangroves positively affect the WTP of the respondents. In contrast, the bid amount and the respondent’s income negatively influence the WTP of the respondents for the mangrove rehabilitation project.